Factors influencing reworks occurrence in construction: a study of selected building projects in Nigeria - L.O. Oyewobi,; D.R. Ogunsemi, (Penerbit UKM, 2010)
Rework has become a menace in Nigerian construction industry and it has not been given required attention, it contributes to time and cost overruns in project. Hence, to improve the performance of projects the research work evaluated rework in some selected building projects in Niger State. The work identified some factors contributing to rework which was categorized under three main headings; technical, quality and human resources factors to actually dig down into the casual of rework. A structure questionnaire was self administered on projects identified to have experienced rework amongst the selected projects and these were ranked according to their perceived degree of severity. Response was further condensed using factor analysis to group the variables into identifiable factors and thus analyzed. The study revealed that sub-standard services rendered by professionals and lack of commitment to quality in term of project delivery by stakeholders are the main source of rework. Therefore, it was recommended that an improvement and total commitment to quality of services render and assurance would lead to a reduction in the occurrence of reworks as revealed by the research.